How do you solve w ^ { 2} - 6w + 9= 13?
2 Answers
Nov 3, 2016
Explanation:
Given:
w^2-6w+9 = 13
Note that the left hand side is already a perfect square trinomial, so we have:
(w-3)^2 = 13
Taking the square root of both sides, allowing for both possible square roots, we have:
w-3 = +-sqrt(13)
Then add
w = 3+-sqrt(13)
Nov 3, 2016
Explanation:
Rearrange
Either use the formula
Where
Or
The other way is completing the square ( which is how the formula is derived)
So
Take the square root of both side